Small ribonucleoprotein particle protein SmD3 governs the homeostasis of germline stem cells and the crosstalk between the spliceosome and ribosome signals in Drosophila. Issue 7 (28th April 2019) - Yu, Jun; Luan, Xiaojin; Yan, Yidan; Qiao, Chen; Liu, Yuanyuan; Zhao, Dan; Xie, Bing; Zheng, Qianwen; Wang, Min; Chen, Wanyin; Shen, Cong; He, Zeyu; et al.
ABSTRACT: The ribonucleoprotein (RNP) spliceosome machinery triggers the precursor RNA splicing process in eukaryotes. Major spliceosome defects are implicated in male infertility; however, the underlying mechanistic links between the spliceosome and the ribosome in Drosophila testes remains largely unresolved. Small ribonucleoprotein particle protein SmD3 (SmD3) is a novel germline stem cell (GSC) regulatory gene identified in our previous screen of Drosophila testes. In the present study, using genetic manipulation in a Drosophila model, we demonstrated that SmD3 is required for the GSC niche and controls the self‐renewal and differentiation of GSCs in the testis. Using in vitro assays in Schneider 2 cells, we showed that SmD3 also regulates the homeostasis of proliferation and apoptosis in Drosophila . Furthermore, using liquid chromatography–tandem mass spectrometry methods, SmD3 was identified as binding with ribosomal protein (Rp)L18, which is a key regulator of the large subunit in the ribosome. Moreover, SmD3 was observed to regulate spliceosome and ribosome subunit expression levels and controlled spliceosome and ribosome function via RpL18. Significantly, our findings revealed the genetic causes and molecular mechanisms underlying the stem cell niche and the crosstalk between the spliceosome and the ribosome.—Yu, J., Luan, X., Yan, Y., Qiao, C, Liu, Y., Zhao, D., Xie, B., Zheng, Q., Wang, M., Chen, W., Shen, C, He, Z., Hu, X., Huang, X., Li, H., Chen, B., Zheng, B., Chen, X., Fang, J. Small ribonucleoprotein particle protein SmD3 governs the homeostasis of germline stem cells and the crosstalk between the spliceosome and ribosome signals in Drosophila . FASEB J. 33, 8125–8137 (2019). www.fasebj.org